APLIKASI BIOCHAR DAN PUPUK KANDANG TERHADAP BUDIDAYA BAWANG MERAH DI TANAH INCEPTISOL KEBUN PERCOBAAN POLITEKNIK PEMBANGUNAN PERTANIAN MEDAN - Tience Elizabet Pakpahan; Taufiq Hidayatullah; Eva Mardiana (Agrica Ekstensia, 2020)
Shallot is an agricultural commodity that has many benefits. It can grow in various habitat types, such as low and high land, paddy fields, home gardens, or even dry land. Biochar is the conversion of agricultural waste through incomplete combustion or pyrolysis into carbon-rich solid material. Utilizing biochar to the soil increases soil fertility because it provides soil nutrients, especially nitrogen, as well as maintaining soil chemicals. This research aim is to identify the effects of biochar application and manure on growth and production of shallot in the reserach field of the Agricultural Development Polytechnic of Medan (Polbangtan Medan). This research was conducted by using a randomized block design and analyzing with ANOVA (5%) and the smallest real difference (5%) as well as using two research parameters which were soil and plant parameters. The initial soil parameters before biochar application were pH, C-organic, N, P and K- total soil, Cation Exchange Capacity (CEC), while plant parameters were height (cm), number of leaves, number of tubers, wet tuber weight per beds (g), wet tuber weights per bed (g). The result revealed that the chemical content of Inceptisol (i.e., pH, CEC, N, P, K, and C-organic) was low and very low. The effect of the biochar and manure was significantly different on the number of leaves and wet tuber weight of shallot. Based on the smallest real difference test showed control was significantly different with biochar of durian peel + manure and biochar of durian peels + biochar of maize on the number of leaves. Furthermore, except biochar of husk + manure on the tuber dry weight, all treatments were significantly different from control on wet tuber weight of shallot. So that, the utilization of biochar can improve soil fertility and shallot production.